GENDER DIFFERENCES OF ODONTOMETRICAL INDICATORS CROWNS OF MOLARS - Vorobec, A.B.; Gasiuk, P.A.; Rosolovska, S.A.; Kostyrenko, O.P. (World of Medicine and Biology, 2016)
Modern reconstructive methods of dentistry (stopping, restoration, prosthetics with different types of orthopedic construction) require of detailed examination of the anatomical structure of the teeth crowns, especially examination of the knowledges about the relief of masticatory surface. That’s why, it was made a detailed examination by us of the features of odontoglyphics of molars according to the gender and determination the odontometrical teeth indicators for the citizens of Ternopil region. To achieve the goals we use the following research methods: odontological, odontometrical and statistical. To perform odontometrical researches, firstly the diagnostical impressions were got from the upper and lower jaw with the help of standard impression tray and alginate impression material («Tropicalgin» brand Zhermack). After the impressions were made the diagnostical models from super plaster (Convertin Hart, type IV brand Spofa-Dental). On these plaster models measuring of the following main parameters of molars were made: measuring mesio-distal, vestibular-lingual crowns sizes, and separately measuring of the hight of clinical crowns separately of the men and women. According to the odontometrical indexes of the sizes of the crowns of molars, women’s processes of reduction are reflected more then men’s. Gender differences of the crowns sizes are specially defined on the second upper and second lower molars. In the result of conducted researches it was given the characteristics of the differences of molars crown’s odontometrical indicators of males and females. The lore of these characteristics playes a great role in the clinic of prosthetic dentistry.
Keywords: odontometry; odontoglyphics drawing; odontologycal status; crowns module